2019
DOI: 10.1186/s40792-019-0634-5
|View full text |Cite
|
Sign up to set email alerts
|

Successful multidisciplinary treatment including repeated metastasectomy for recurrent squamous cell esophageal carcinoma: a case report

Abstract: Background Recurrences after radical esophagectomy are common. The prognosis for recurrent esophageal cancer is generally poor. Recurrences usually occur between 1 and 3 years of surgery, with the duration of median survival after recurrence ranging from 5 to 10 months. The number of sites and involved organs vary among patients. Consequently, a standard therapeutic strategy has not been established, and the role of surgery in the management of recurrence is unclear. Case presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…With regard to multiple lines of active treatment, there have been several case reports of successful multidisciplinary treatment in recurrent and metastasis esophageal cancer patients, with therapy modalities including but not limited to salvage surgery, chemoradiotherapy, radiofrequency ablation, and hepatic arterial infusions. [10][11][12][13] Some population studies on second-and third-line chemotherapy have reported prolonged PFS, higher objective response rate, or higher 6-month survival rate; nonetheless, the OS has been disappointing. 14,16 Thus, the evidence for the benefits of salvage treatment and therapy modality options is inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to multiple lines of active treatment, there have been several case reports of successful multidisciplinary treatment in recurrent and metastasis esophageal cancer patients, with therapy modalities including but not limited to salvage surgery, chemoradiotherapy, radiofrequency ablation, and hepatic arterial infusions. [10][11][12][13] Some population studies on second-and third-line chemotherapy have reported prolonged PFS, higher objective response rate, or higher 6-month survival rate; nonetheless, the OS has been disappointing. 14,16 Thus, the evidence for the benefits of salvage treatment and therapy modality options is inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…9 Our study was the first to systematically explore the association between multiple lines of active therapy and prognosis in ESCC patients. [10][11][12][13][14]…”
Section: Introductionmentioning
confidence: 99%